Practical Pedagogic in Basic to High Schools as The Field of Democratic Education Management in Timor-Leste - João da Silva; Erni Silvia Ximenes; Virgina Martins; Aurea Elisabete Araujo Fatima Amaral; Jeferino da Costa Brandao (Green Publisher, 2026)
The practical pedagogy in basic to high school serves as the focus of research on democratic education management in Timor-Leste. The purpose of this research is to pinpoint the issues and obstacles or recommendations for forthcoming studies. The technical approach of this qualitative descriptive research analysis employs online research through digital library resources, journals, or printed materials, along with supplementary field research at the Ensino Básico 30 Ciclo Santo Luis Gonzaga school, located in Debos, Suai Covalima district. The participants in this study included a school principal, two teachers representing a total of 15 respondents, and two students representing 350 students at the school, in order to present the data for analysis. The data collection activities occurred in 2025 at the site of this research by administering the questionnaire forms to the participants. The outcome and discovery of this research highlight issues faced by schools, including challenges such as the shortage of teaching personnel resulting from the education Ministry's political policy to temporarily cease the employment of many teachers in the area due to innovations and reforms aimed at improving and enhancing the quality of education in Timor-Leste. The education system is offered to everyone equally, accessible to all without discrimination, in accordance with the state constitution and the enforcement of human rights laws in Timor-Leste.